The tear film characteristics of spontaneous subconjunctival hemorrhage patients detected by Schirmer test I and tear interferometry - Liu, Wei (Molecular Vision, 2012)
PURPOSE: To evaluate the tear film characteristics of spontaneous subconjunctival hemorrhage patients by Schirmer test I and tear interferometry. METHODS: Forty-six spontaneous subconjunctival hemorrhage patients and 46 controls were enrolled in the study. Schirmer test I and tear interferometry were performed in all 92 subjects. The results obtained were compared between the two groups. RESULTS: The Schirmer test I value of the spontaneous subconjunctival hemorrhage patients was 6.93 (4.72) mm, and that of the controls was 14.70 (3.70) mm. A statistical difference was found between the two groups (independent samples t test, t=-8.79, p<0.001). The mean rank of the tear interferometry patterns of the spontaneous subconjunctival hemorrhage patients was 50.07, and that of the controls was 42.93. No statistical difference was found between the two groups (Mann–Whitney U test, Z=-1.85, p=0.064). CONCLUSIONS: For the spontaneous subconjunctival hemorrhage patients, the Schirmer test I value was lower than that of the controls, whereas the tear interferometry patterns were comparable to that of the controls.